MODELS OF ESTIMATING EFFICIENCY OF TRANSPORT MODES - Омельченко, О. Д.; Сулима, Л. О.; Соколова, О. Є. (Science-based technologies, 2019)
The article deals with the application of classical types of models to assessing the efficiency of transport modes for medium and long distances, namely, aviation and railway in modern conditions of the air transport system operation. Assessment of the efficiency of these transport modes has been carried out from the passenger’s viewpoint; therefore, the following efficiency criteria have been taken into account: travel time, the cost of travel; as well as how the passenger assesses the cost of the hour which he will spend on this trip. A passenger’s trip has been compared with a typical low-cost airline and European train, considering the ticket prices and travel time which are now very close to these transport modes and accessible to passengers. The models of assessing the use of railway and aviation transport modes have been studied in detail, namely, the classification of an average passenger’s transport mode choice by has been developed. In this article, the calculation has been conducted on the basis of the following models: Freiman’s three-alternative model; Freiman’s three-alternative model with taking into account the passenger’s assessment of the trip’s appropriateness; the three-alternative model based on normal approximation. It was exactly the three-alternative models which have been applied, because there is a significant lack of two-alternative models – a relatively small number of the factors taken into account. Even more accurate models are based on normal approximation. These models have been tested with the purpose of combining classical and modern approaches to study the assessment of the transport modes efficiency in the conditions of the current transport system’s functioning. The comparison has shown the results based on the three compared models are close. In this work we have decided to consider the road transport as a delivery one for this kind of distances (medium and long). Automobile transport mode has not been compared with railroad and aviation ones, because the authors consider it to be ineffective for these distances, which coincides with the opinion of the other scientists. The further perspective research areas have to cover the study of competitive advantages of aviation low-cost traffic and the European train transportations for medium and long distances in connection with the increase in rail ridership in the direction of European countries after implementing the visa-free regime with the European Union.